EMPOWERMENT OF ZAKAT IN ORDER TO ERADICATE POVERTY OF THE PEOPLE (STUDY ACCORDING TO LAW 23 OF 2011 CONCERNING ZAKAT MANAGEMENT) - Niamulloh, Niamulloh (Jurnal Hukum Khaira Ummah, 2023)
The main purpose of the existence of zakat is so as not to gap in the social life of the community, so that will be established a good relationship among fellow human beings. Zakat is projected to achieve a variety of strategic objectives, among them to improve the welfare of the mustahiq (beneficiaries of zakat) especially the poor, actualization of potential funds to build the ummah, build educational facilities, health facilities, create tranquility, happiness, security and prosperity of life. To achieve that goal the zakat must be rightly empowered. Then the zakat funds are given really appropriate to relate to the program of empowerment that is able to overcome the problem of poverty.Keywords: zakat, empowerment, poverty